Tinjauan Fatwa DSN No. 49/DSN MUI/II/2005 tentang Konversi Akad dan PBI No. 10/18/PBI/2008 tentang Restrukturisasi Pembiayaan bagi BUS dan UUS terhadap Pelaksanaan Konversi Akad pada Bank X - Lusi Kholisiah; Zaini Abdul Malik; Encep Abdul Rojak (Bandung Conference Series: Sharia Economic Law, 2021)
Abstract. The implementation of contract conversion on MMQ financing to Murabahah contracts in the KPR program at BSI KC Tasikmalaya is indicated not to have been based on the MUI fatwa and regulations issued by Bank Indonesia in full due to several complaints from several customers regarding the difference or difference in the nominal selling price of large financing objects. Based on the background of the problem, the purpose of this study is to find out and analyze the review of the Fatwa of DSN NO. 49/DSN MUI/II/2005 concerning Akad Conversion and PBI NO. 10/18/PBI/2008 concerning Financing Restructuring for BUS and UUS for the conversion of MMQ contracts to murabahah contracts in the KPR program at BSI KC Tasikmalaya. The research method used in this research is analytical descriptive with a qualitative data analysis approach, namely examining the implementation of the MMQ contract conversion to the murabahah contract at BSI Tasikmalaya in terms of the provisions of the Fatwa DSN NO.49/DSN MUI/II/2005 and PBI NO.10/18/PBI/2008. The results of this study indicate that the implementation of the conversion of the MMQ contract which was changed to the murabahah contract at BSI Tasikmalaya branch was in accordance with the provisions of the murabahah contract conversion according to the DSN-MUI Fatwa Number: 49/DSN-MUI/11/2005 concerning Murabahah Contract Conversion and PBI PBI NO. 10/18/PBI/2008 concerning Financing Restructuring for BUS and UUS. Abstrak. Pelakanaan konversi akad pada pembiayaan MMQ kepada akad Murabahah dalam program KPR di BSI KC Tasikmalaya terindikasi dilakukan belum berdasarkan fatwa MUI dan aturan yang dikeluarkan oleh Bank Indonesia banyaknya keluhan dari para nasabah terkait selisih atau perbedaan nominal harga jual objek pembiayaan yang besar. Berdasarkan permasalahan tersebut, maka tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis tinjauan Fatwa DSN NO. 49/DSN MUI/II/2005 Tentang Konversi Akad dan PBI NO. 10/18/PBI/2008 Tentang Restrukturisasi Pembiayaan Bagi BUS dan UUS terhadap pelaksanaan konversi akad MMQ kepada akad murabahah pada program KPR di BSI KC Tasikmalaya. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif analitis dengan pendekatan analisa data secara kualitatif yaitu meneliti pelaksanaan konversi akad MMQ kepada akad murabahah di BSI Tasikmalaya ditinjau dari ketentuan Fatwa DSN NO. 49/DSN MUI/II/2005 dan PBI NO. 10/18/PBI/2008. Hasil penelitian ini menujukkan bahwa pelaksanaan konversi akad MMQ yang diubah kepada akad murabahah di BSI KC Tasikmalaya telah sesuai dengan ketentuan konversi akad murabahah menurut Fatwa DSN-MUI Nomor : 49/DSN-MUI/11/2005 Tentang Konversi Akad Murabahah dan PBI PBI NO. 10/18/PBI/2008 Tentang Restrukturisasi Pembiayaan Bagi BUS dan UUS.